Spectral fluence of neutrons generated by radiotherapeutic linacs - Králík, Miloslav; Šolc, Jaroslav; Vondráček, Vladimir; Šmoldasová, Jana; Farkašová, Estera; Tichá, Ivana (Radiation protection dosimetry, 2015)
Spectral fluences of neutrons generated in the heads of the radiotherapeutic linacs Varian Clinac 2100 C/D and Siemens ARTISTE were measured by means of the Bonner spheres spectrometer whose active detector of thermal neutrons was replaced by an activation detector, i.e. a tablet made of pure manganese. Measurements with different collimator settings reveal an interesting dependence of neutron fluence on the area defined by the collimator jaws. The determined neutron spectral fluences were used to derive ambient dose equivalent rate along the treatment coach. To clarify at which components of the linac neutrons are mainly created, the measurements were complemented with MCNPX calculations based on a realistic model of the Varian Clinac.
Keywords: dávka záření; Scattering, Radiation; Equipment Failure Analysis; částice - urychlovače; Models, Statistical; Equipment Design; Neutrons; Computer Simulation; neutrony; design s pomocí počítače; radiometrie; statistické modely; radiochirurgie; design vybavení; Radiation Dosage; Monte Carlo Method; Computer-Aided Design; Radiometry; metoda Monte Carlo; radiační rozptyl; Particle Accelerators; počítačová simulace; Radiosurgery; analýza selhání vybavení